Drivers of healthcare costs associated with the episode of care for surgical aortic valve replacement versus transcatheter aortic valve implantation - Wijeysundera, Harindra C (Open Heart, 2016)
OBJECTIVE: Transcatheter aortic valve implantation (TAVI) is generally more expensive than surgical aortic valve replacement (SAVR) due to the high cost of the device. Our objective was to understand the patient and procedural drivers of cumulative healthcare costs during the index hospitalisation for these procedures. DESIGN: All patients undergoing TAVI, isolated SAVR or combined SAVR+coronary artery bypass grafting (CABG) at 7 hospitals in Ontario, Canada were identified during the fiscal year 2012–2013. Data were obtained from a prospective registry. Cumulative healthcare costs during the episode of care were determined using microcosting. To identify drivers of healthcare costs, multivariable hierarchical generalised linear models with a logarithmic link and γ distribution were developed for TAVI, SAVR and SAVR+CABG separately. RESULTS: Our cohort consisted of 1310 patients with aortic stenosis, of whom 585 underwent isolated SAVR, 518 had SAVR+CABG and 207 underwent TAVI. The median costs for the index hospitalisation for isolated SAVR were $21 811 (IQR $18 148–$30 498), while those for SAVR+CABG were $27 256 (IQR $21 741–$39 000), compared with $42 742 (IQR $37 295–$56 196) for TAVI. For SAVR, the major patient-level drivers of costs were age >75 years, renal dysfunction and active endocarditis. For TAVI, chronic lung disease was a major patient-level driver. Procedural drivers of cost for TAVI included a non-transfemoral approach. A prolonged intensive care unit stay was associated with increased costs for all procedures. CONCLUSIONS: We found wide variation in healthcare costs for SAVR compared with TAVI, with different patient-level drivers as well as potentially modifiable procedural factors. These highlight areas of further study to optimise healthcare delivery.